Üniversite Öğrencilerinin Girişimcilik Düzeylerini Belirlemeye Yönelik Bir Araştırma - Honça, Ayşe Aslı; Çeti̇nkaya, Turan (OPUS - Uluslararasi Toplum Arastirmalari Dergisi, 2019)
The purpose of this study is to examine theentrepreneurship level of university students in terms of several factors. TheEntrepreneurship Scale, which was developed by Yılmaz and Sünbül (2009), hasbeen used as the data collecting tool of the study used on descriptive surveymethod. The students who receive education in the School of Physical Educationand Sports in Kastamonu and Ahi Evran Universities constitute the population ofthe study. The sample of the study consisted of 325 volunteer participantsdetermined by the sampling method. Descriptive statistics, Mann Whithey U andKruskal Wallis methods were used in data analysis. According to the findings ofthe study, it was found out that the university students have high level ofentrepreneurship. Besides, when the correlations between the entrepreneurshiplevel of university students and level of income, age and university variablesare examined, it has been determined that there are statistically significantdifferences. On the other hand, there is no significant difference between theentrepreneurship level of university students and gender, department and gradevariables.

Buaraştırmanın amacı, üniversite öğrencilerinin girişimcilik düzeylerini çeşitlifaktörler açısından incelemektir. Betimsel tarama yöntemi kullanılan araştırmadaveri toplama aracı olarak, Yılmaz ve Sünbül (2009) tarafından geliştirilenGirişimcilik Ölçeği kullanılmıştır. Araştırmanın evrenini Kastamonu ve AhiEvran Üniversiteleri Beden Eğitimi ve Spor Yüksekokulları'nda öğrenim görenöğrenciler oluşturmaktadır. Araştırmanın örneklemini ise, kolayda örneklemeyöntemi ile belirlenmiş 325 gönüllü katılımcı oluşturmaktadır. Verilerinanalizinde tanımlayıcı istatistikler, Mann Whithey U ve Kruskal Wallisyöntemleri kullanılmıştır. Araştırmanın bulgularına göre, üniversiteöğrencilerinin girişimcilik düzeyinin yüksek olduğu tespit edilmiştir. Ayrıca,üniversite öğrencilerinin girişimcilik düzeyi ile gelir düzeyi, yaş veüniversite değişkenleri arasındaki ilişki incelendiğinde, istatistiksel olarakanlamlı farklılıklar olduğu tespit edilmiştir. Diğer taraftan, üniversiteöğrencilerinin girişimcilik düzeyi ile cinsiyet, bölüm ve sınıf değişkenleriarasında anlamlı bir fark bulunmamaktadır.
Keywords: University students; Entrepreneurship; Level of entrepreneurship; Girişimcilik; Üniversite öğrencisi; Girişimcilik düzeyi; 4. Education; 8. Economic growth